TSPO imaging-guided characterization of the immunosuppressive myeloid tumor microenvironment in patients with malignant glioma. Issue 7 (12th February 2020) - Zinnhardt, Bastian; Müther, Michael; Roll, Wolfgang; Backhaus, Philipp; Jeibmann, Astrid; Foray, Claudia; Barca, Cristina; Döring, Christian; Tavitian, Bertrand; Dollé, Frédéric; Weckesser, Matthias; Winkeler, Alexandra; et al.
Abstract: Background: Tumor-associated microglia and macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) are potent immunosuppressors in the glioma tumor microenvironment (TME). Their infiltration is associated with tumor grade, progression, and therapy resistance. Specific tools for image-guided analysis of spatiotemporal changes in the immunosuppressive myeloid tumor compartments are missing. We aimed (i) to evaluate the role of fluorodeoxyglucose ( 18 F)DPA-714* (translocator protein [TSPO]) PET-MRI in the assessment of the immunosuppressive TME in glioma patients, and (ii) to cross-correlate imaging findings with in-depth immunophenotyping. Methods: To characterize the glioma TME, a mixed collective of 9 glioma patients underwent [ 18 F]DPA-714-PET-MRI in addition to [ 18 F]fluoro-ethyl-tyrosine (FET)-PET-MRI. Image-guided biopsy samples were immunophenotyped by multiparametric flow cytometry and immunohistochemistry. In vitro autoradiography was performed for image validation and assessment of tracer binding specificity. Results: We found a strong relationship ( r = 0.84, P = 0.009) between the [ 18 F]DPA-714 uptake and the number and activation level of glioma-associated myeloid cells (GAMs). TSPO expression was mainly restricted to human leukocyte antigen D related–positive (HLA-DR+) activated GAMs, particularly to tumor-infiltrating HLA-DR+ MDSCs and TAMs. [ 18 F]DPA-714–positive tissue volumes exceeded [ 18 F]FET-positive volumes and showed a differential spatial distribution. Conclusion: [ 18 F]DPA-714-PET may be used to non-invasively image the glioma-associated immunosuppressive TME in vivo. This imaging paradigm may also help to characterize the heterogeneity of the glioma TME with respect to the degree of myeloid cell infiltration at various disease stages. [ 18 F]DPA-714 may also facilitate the development of new image-guided therapies targeting the myeloid-derived TME.